2020
DOI: 10.1128/aem.01782-20
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Transporters and Glycoside Hydrolases Are Involved in Arabinoxylan-Derived Oligosaccharide Utilization in Bifidobacterium pseudocatenulatum

Abstract: Arabinoxylan hydrolysates (AXH) are the hydrolyzed products of the major components of dietary fibers, arabinoxylan. AXH include diverse oligosaccharides varying in xylose polymerization and side residue modifications with arabinose at the O-2 and/or O-3 positions of the xylose unit. Previous studies have reported that AXH exhibit prebiotic properties on gut bifidobacteria; moreover, several adult-associated bifidobacterial species (e.g., Bifidobacterium adolescentis and Bifidobacterium longum ssp. longum) are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…Previous studies have identified several GH43 family enzymes in bifidobacteria that degrade xylan-related carbon sources [ 36 ]. In addition, the enzymes belonging to GH8, GH10, and GH120 families may also participate in XOS or xylan degradation [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have identified several GH43 family enzymes in bifidobacteria that degrade xylan-related carbon sources [ 36 ]. In addition, the enzymes belonging to GH8, GH10, and GH120 families may also participate in XOS or xylan degradation [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, two β-xylosidase, XylB from GH120 family and XylC from GH43 family, with different specificities have been in vitro characterized in B. adolescentis [ 64 ]. Recent study has also characterized three xylosidases from GH43 family in B. pseudocatenulatum and these enzymes exhibit functionally identical activity in XOS degradation [ 36 ]. Moreover, extracellular β-xylanase (GH10) may provide some B. pseudocatenulatum strains stronger long-chain xylan utilization abilities.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this observation, experimental study showed that B . pseudocatenulatum could utilize several components of arabinoxylan hydrolysates (AXH) via the upregulation of three GH43-ABC transporter clusters ( 43 ). This feature likely explains the abundance and persistence of B .…”
Section: Discussionmentioning
confidence: 99%
“…Our results reiterate previous findings on the genomic characterization of the Bifidobacterium genus (6) and Bp in the European population (33), showing that the species harbors an expansive repertoire of enzymes (GH13, GH43) responsible for the assimilation of complex plant-derived carbohydrates, but not host-derived glycan (mucin, HMO). In line with this observation, experimental study showed that Bp could utilize several components of arabinoxylan hydrolysates (AXH), via the upregulation of three GH43 -ABC transporter clusters (34). This feature likely explains the abundance and persistence of Bp through adulthood in the Vietnamese gut microbiota, since the organism may thrive on non-digestible carbohydrates enriched with fruits and vegetables.…”
Section: Discussionmentioning
confidence: 77%